2014
DOI: 10.3390/molecules191221350
|View full text |Cite
|
Sign up to set email alerts
|

Is Development of High-Grade Gliomas Sulfur-Dependent?

Abstract: Abstract:We characterized γ-cystathionase, rhodanese and 3-mercaptopyruvate sulfurtransferase activities in various regions of human brain (the cortex, thalamus, hypothalamus, hippocampus, cerebellum and subcortical nuclei) and human gliomas with II to IV grade of malignancy (according to the WHO classification). The human brain regions, as compared to human liver, showed low γ-cystathionase activity. The activity of rhodanese was also much lower and it did not vary significantly between the investigated brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 35 publications
6
52
0
Order By: Relevance
“…We have recently shown that higher cystathionine levels are associated with 1p/19q codeletion and that cystathionine could represent a noninvasive marker of abnormal expression of cystathionine‐pathway genes such as cystathionine gamma‐lyase and cystathionine beta‐synthase . In a previous ex vivo study, the changed profile of cystathionine gamma‐lyase activity and cystathionine levels in gliomas were correlated, and both of them decreased with the increase of the grade of glioma malignancy . Additionally, our observations suggested that cystathionine increase is associated with enhanced cystathionine beta‐synthase activity likely due to a compensatory mechanism induced by oxidative stress, and that this process may be exacerbated in the presence of 1p/19q codeletion due to reduced activity of cystathionine gamma‐lyase (located on chromosome 1p) .…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We have recently shown that higher cystathionine levels are associated with 1p/19q codeletion and that cystathionine could represent a noninvasive marker of abnormal expression of cystathionine‐pathway genes such as cystathionine gamma‐lyase and cystathionine beta‐synthase . In a previous ex vivo study, the changed profile of cystathionine gamma‐lyase activity and cystathionine levels in gliomas were correlated, and both of them decreased with the increase of the grade of glioma malignancy . Additionally, our observations suggested that cystathionine increase is associated with enhanced cystathionine beta‐synthase activity likely due to a compensatory mechanism induced by oxidative stress, and that this process may be exacerbated in the presence of 1p/19q codeletion due to reduced activity of cystathionine gamma‐lyase (located on chromosome 1p) .…”
Section: Discussionsupporting
confidence: 56%
“…Higher cystathionine levels in brain tumors compared to normal tissue were reported previously from ex vivo tissue analysis . In particular, tumors of glial origin showed the highest cystathionine concentrations, suggesting that cystathionine is preferentially synthesized in glial cells .…”
Section: Introductionmentioning
confidence: 45%
See 2 more Smart Citations
“…Further studies are awaited to clarify the mechanisms of responses to H 2 S that are conflicting depending on the type of cancer. Wrobel et al (2014) reported that the levels of sulfane sulfur (polysulfides) in gliomas with the highest grades of malignancy are greater than those of glioma-free brain regions. A similar result was also reported in glioblastoma-bearing ipsilateral hemispheres, which contain greater amounts of H 2 S n than the glioblastoma-free control hemispheres (Shiota et al, 2018).…”
Section: Production Of Cysssh and Gsshmentioning
confidence: 99%